(untitled) (PJDOL, 2023)
In this research, the author presents the lived experience of a graduate student and how she has overcome the feeling of isolation and challenges in distance learning. The participant of this qualitative phenomenological study is student from Visayas State University Open University (VSU-OU). This qualitative phenomenological study (Chambers, 2013) seeks to measure the in-depth experience of a distance learner from the southern Philippines and systematically analyze the culture of distance learning in order to understand the phenomenon of isolation and be able to share in future studies.